Government Policy, Innovation Capability, Internal Environment and Its Influence on the Business Performance of Craftsmen at the Silver Handicraft Industry Clushter in Pasuruan Regency - Arga Christian Sitohang; Bambang Wiwoho (LPPM of NAROTAMA UNIVERSITY, 2022)
This study aims to explain Government Policy, Internal Environmental, Innovation Capability, and Its Influence on the Business Performance of Craftsmen at the Silver Handicraft Industry Clushter in Pasuruan Regency. The research model with hypothesis development was derived based on the literature. To provide empirical evidence, this study conducted a survey, using primary data collected using a list of questionnaires, and saturated sampling of 50 craftsmen at the Silver Handicraft Industry Clushter in Pasuruan Regency. The results showed that Government Policy had an insignificant effect, Innovation Ability had a positive and significant effect, Internal Environment had a positive and significant effect on employee performance at the Silver Handicraft Industry Center in Pasuruan Regency. The results of this study do not support the research of Hafizah, et al (2017), Putra and Bayu (2017), Wisardja (2000), Yonggui, et al. (2000), Fogel (2001), Poisson, et al. (2002), Saxby, et al. (2002), Prasetyo (2003), Supriyono and Setiawan (2004), Mujali (2004), Ngamkroeckjoti, et al (2005), Pettus, et al. (2007), Rodrigues and Esteves (2007). The implication of the research is to examine the perceptions of 50 employees at the Brem Small Industry Clushter in Pasuruan Regency. The analytical technique used is multiple linear regression.